Mental health services use among Canadian Armed Forces members and Veterans: Data from the 2018 Canadian Armed Forces members and Veterans mental health follow-up survey (CAFMVHS) - St. Cyr, Kate; Liu, Aihua; Plouffe, Rachel A.; Nouri, Maede S.; Forchuk, Callista A.; Wanklyn, Sonya G.; Bird, Brian M.; Fikretoglu, Deniz; Mahar, Alyson L.; Nazarov, Anthony; Richardson, J. Don (Frontiers in Health Services, 2022)
Background Differences in healthcare delivery systems and pathways to mental healthcare for Canadian Armed Forces (CAF) members and Veterans may contribute to variations in mental health services use (MHSU) and the factors associated with it. We: (1) estimated the prevalence of past 12-month MHSU (≥1 visit with a medical or mental health professional); and (2) identified sociodemographic, military-, trauma-, and health-related variables associated with MHSU among CAF members and Veterans. Methods The current study used data from the 2018 CAF Members and Veterans Mental Health Follow-Up Survey (CAFVMHS). Model variables were selected a priori, and their respective associations with MHSU were estimated among (1) CAF members and (2) Veterans using separate multivariable logistic regression models. Results Similar proportions of CAF members and Veterans reported past 12-month MHSU (26.9 vs. 27.5%, respectively). For both CAF members and Veterans, meeting criteria for at least one past 12-month MH disorder was associated with past 12-month MHSU [adjusted odds ratio (AOR) = 7.80, 95% confidence interval (CI) = 7.18–8.46; and AOR = 11.82, 95% CI: 11.07–12.61, respectively). Past-year suicide ideation, a history of sexual trauma, and endorsement of adverse childhood experiences were also significantly associated with MHSU among CAF members and Veterans. Significance Similar to previous research, meeting screening criteria for a past 12-month MH disorder was strongly associated with MHSU among both samples. This study extends our existing knowledge about factors associated with MHSU among CAF members and Veterans, and offers direction for future research to increase MHSU.